THE IMPACT OF SOME SOCIO-ECONOMIC INDICATORS ON INDUSTRIAL DEVELOPMENT IN SURKHANDARYA (Archive of Conferences, 2022)
In this abstract evaluated the effect of important socio-economic indicators on the development of industry sector in Surkhan region